PENGARUH PENDEKATAN INKUIRI TERSTUKTUR TERHADAP MOTIVASI DAN KEMANDIRIAN BELAJAR SISWA - Ronauli Simanullang; Nada Sibuea (Komunitas Manajemen Kompetitif, 2025)
his study aims to examine the effect of the structured inquiry approach on students’ learning motivation and learning independence. The background of this research lies in the low motivation and independence of students caused by teacher-centered instructional practices. The structured inquiry approach was chosen because it provides clear steps while encouraging students to actively engage in the investigation process. Data were collected through motivation and learning independence questionnaires as well as classroom observations.The structured inquiry approach proved effective in creating meaningful learning experiences and fostering active student involvement. Therefore, it can be concluded that the structured inquiry approach has a positive effect on students’ motivation and learning independence. This approach is recommended as an alternative instructional strategy to enhance the overall quality of learning in schools.